2020
DOI: 10.1126/science.abc5534
|View full text |Cite
|
Sign up to set email alerts
|

A cortex-like canonical circuit in the avian forebrain

Abstract: Although the avian pallium seems to lack an organization akin to that of the cerebral cortex, birds exhibit extraordinary cognitive skills that are comparable to those of mammals. We analyzed the fiber architecture of the avian pallium with three-dimensional polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
173
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(186 citation statements)
references
References 72 publications
1
173
1
Order By: Relevance
“…Recent descriptions of the anatomical organization of the visual and auditory areas of DVR have shown that both these regions share a common laminar/columnar cytoarchitecture, comparable in their organization to the one entailed in mammalian sensory cortices. Whether nucleus basorostralis pallii and the internal portion of its overlying mesopallial zone, along with a columnar organization of the cells in this region (Dubbeldam & Visser, 1987;Stacho et al, 2020). The detailed description obtained by us using up-to-date neural tracing methods confirmed and extended these previous results and established the extent to which a "canonical" pallial circuitry can be found in all sensory areas of the avian DVR.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Recent descriptions of the anatomical organization of the visual and auditory areas of DVR have shown that both these regions share a common laminar/columnar cytoarchitecture, comparable in their organization to the one entailed in mammalian sensory cortices. Whether nucleus basorostralis pallii and the internal portion of its overlying mesopallial zone, along with a columnar organization of the cells in this region (Dubbeldam & Visser, 1987;Stacho et al, 2020). The detailed description obtained by us using up-to-date neural tracing methods confirmed and extended these previous results and established the extent to which a "canonical" pallial circuitry can be found in all sensory areas of the avian DVR.…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, both these regions appear organized as complexes of laminarly arranged cell groups highly interconnected in a "laminar/columnar" fashion, in such a way that cells located in homotopic positions in each of the forming layers (senso-recipient nidopallium, intermediate nidopallium, and ventral mesopallium) are reciprocally linked by a local loop of axonal processes running across these layers (Ahumada-Galleguillos et al, 2015;Fern andez, Ahumada-Galleguillos, et al, 2020;Wang et al, 2010). Interestingly, such laminar/columnar arrangement bears a striking resemblance to that of the mammalian sensory cortices at laminar, cellular and intrinsic circuitry levels (Dugas-Ford et al, 2012;Faunes et al, 2015;Jarvis et al, 2013;Karten, 2015;Stacho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From a neurobiological perspective, most studies on number cognition focused on primates' cortical areas and on the nidopallium caudolaterale (NCL) of corvids, which is supposed to be equivalent to the primates' prefrontal cortex (Mogensen and Divac, 1982;Divac et al, 1985;Güntürkün, 2005;Nieder, 2018;Stacho et al, 2020). In comparison, few studies investigated the contribution of subcortical (sub-pallial) regions.…”
Section: Numerosities and Other Kind Of Magnitudes In The Brainsmentioning
confidence: 99%
“…Clarifying the degree to which these patterns extend across vertebrates requires examining other episodes of encephalization. Crown birds offer an excellent comparative system to mammals, even primates, because they share neuroanatomical features that evolved independently, including a relatively large brain size ( Jerison, 1973 ; Nieuwenhuys et al, 1998 ; Northcutt, 2002 ; Butler and Hodos, 2005 ; Iwaniuk et al, 2005 ; Gill, 2006 ), globular brains with expanded cerebra, specialized cytoarchitecture and neuron types ( Reiner et al, 2004 ; Dugas-Ford et al, 2012 ; Shanahan et al, 2013 ; Pfenning et al, 2014 ; Karten, 2015 ; Stacho et al, 2020 ), and the capacity to perform higher cognitive behaviors ( Lefebvre et al, 2002 ; Weir et al, 2002 ; Emery, 2006 ; Auersperg et al, 2012 ; Kabadayi et al, 2016 ; Bayern et al, 2018 ; Boeckle et al, 2020 ). In addition, they feature remarkable variation in brain morphology that is conducive to macroevolutionary studies ( Iwaniuk and Hurd, 2005 ; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%